2021
DOI: 10.3390/electronics10010083
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturized Antipodal Vivaldi Antenna with Improved Bandwidth Using Exponential Strip Arms

Abstract: In this paper, a miniaturized ultra-wideband antipodal tapered slot antenna with exponential strip arms is presented. Two exponential arms with designed equations are optimized to reduce the lower edge cut-off frequency of the impedance bandwidth from 1480 MHz to 720 MHz, resulting in antenna miniaturization by 51%. This approach also improves antenna bandwidth without compromising the radiation characteristics. The dimension of the proposed antenna structure including the feeding line and transition is 158 × … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Dimensions are represented in terms of the center frequency of the antenna. The antenna designed in [31,32] provides a very good bandwidth, but its gain variation is higher, and the antenna size is also very large. In [33,34] an antenna is designed with a wide bandwidth and moderate antenna size, but its gain is small.…”
Section: Resultsmentioning
confidence: 99%
“…Dimensions are represented in terms of the center frequency of the antenna. The antenna designed in [31,32] provides a very good bandwidth, but its gain variation is higher, and the antenna size is also very large. In [33,34] an antenna is designed with a wide bandwidth and moderate antenna size, but its gain is small.…”
Section: Resultsmentioning
confidence: 99%
“…The size and fractional bandwidth of the proposed antenna in this work is superior to that of the reported work in [ 28 , 29 , 30 ], as shown in Table 2 . Although, the proposed antenna in [ 31 , 32 , 33 , 34 ] possess better gain and fractional bandwidth; nonetheless, with larger size, more expensive substrate, and worse group delay property. It can be observed that the proposed antenna has the advantages in compact size, fractional ultra-wide bandwidth, low cost, and good enough merit of gain.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, a typical AVA was modified, simulated, and developed at 5-40 GHz, and next the dimensions were optimized. Particularly, exponential patch and feed line dimensions were calculated applying the formulas provided in [56,57]. The proposed antenna includes two main tapered strips (conventional structure) and three additional curved-strip arms.…”
Section: Mavamentioning
confidence: 99%